An overlooked new species of Croton section Geiseleria (Euphorbiaceae) from the Brazilian Cerrado, with a key to the species of this section occurring in the state of Goiás and in the Distrito Federal - Sodré, Rodolfo Carneiro; Da Silva, Marcos José (Phytotaxa, 2017)
As currently circumscribed, Croton section Geiseleria comprises ca. 80 species and is one of the three largest American sections of the genus. During studies of this section in midwestern Brazil, we discovered several specimens in the highlands of the state of Goiás and Federal District that correspond to a new species. Croton ramosissimus is herein described and illustrated. The morphological affinities, preliminary conservation status, and period of flowering and fruiting of this species are also presented. The novel species is more morphologically similar to C. tamberlikii, and differs from it by having diffuse and densely ramified stems, leaves with prominent venation on the abaxial surface, minute bracts (up to 2.7 mm long), villous stamens, and oblongoid seeds without spots, among other characteristics. A key to identify 22 species of Croton section Geiseleria that occur in the state of Goiás and Federal District is also provided, with images for 20 of them.